VDC_100102370104.0X000001. Issue 2 (February 2018) - Rosemurgy, Alexander; Downs, Darrell; Luberice, Kenneth; Rodriguez, Christian; Swaid, Forat; Patel, Krishen; Toomey, Paul; Ross, Sharona
This study was undertaken to determine whether postoperative outcomes after laparoscopic Heller myotomy with anterior fundoplication could be predicted by preoperative findings on esophagography. Preoperative barium esophagograms of 135 patients undergoing laparoscopic Heller myotomy with anterior fundoplication were reviewed. The number of esophageal curves, esophageal width, and angulation of the gastroesophageal junction (GEJ) were determined; correlations between these determined parameters and symptoms were assessed using linear regression analysis. The number of esophageal curves correlated with the preoperative frequency of dysphagia, vomiting, chest pain, regurgitation, and heartburn. The width of the esophagus negatively correlated with the preoperative frequency of regurgitation. The angulation of the GEJ did not correlate with preoperative symptoms. Laparoscopic Heller myotomy with anterior fundoplication significantly reduced the frequency and severity of all symptoms, regardless of the number of esophageal curves, esophageal width, or angulation of the GEJ. Laparoscopic Heller myotomy with anterior fundoplication provides dramatic palliation for achalasia. More esophageal curves on preoperative esophagography correlate well with the frequency of a broad range of preoperative symptoms, including the frequency of dysphagia and regurgitation. Patients experience dramatically improved frequency and severity of symptoms after laparoscopic Heller myotomy with anterior fundoplication for achalasia regardless of the number of esophageal curves, esophageal width, or the angulation of the GEJ. Findings on barium esophagogram, in evaluating achalasia, should not deter the application of laparosocopic Heller myotomy with anterior fundoplication.